Allyl isothiocyanate affects the cell cycle of Arabidopsis thaliana - Åsberg, Signe E.; Bones, Atle M.; Øverby, Anders (Frontiers in Plant Science, 2015)
Isothiocyanates (ITCs) are degradation products of glucosinolates present in members of the Brassicaceae family acting as herbivore repellents and antimicrobial compounds. Recent results indicate that allyl ITC (AITC) has a role in defense responses such as glutathione depletion, ROS generation and stomatal closure. In this study we show that exposure to non-lethal concentrations of AITC causes a shift in the cell cycle distribution of Arabidopsis thaliana leading to accumulation of cells in S-phases and a reduced number of cells in non-replicating phases. Furthermore, transcriptional analysis revealed an AITC-induced up-regulation of the gene encoding cyclin-dependent kinase A while several genes encoding mitotic proteins were down-regulated, suggesting an inhibition of mitotic processes. Interestingly, visualization of DNA synthesis indicated that exposure to AITC reduced the rate of DNA replication. Taken together, these results indicate that non-lethal concentrations of AITC induce cells of A. thaliana to enter the cell cycle and accumulate in S-phases, presumably as a part of a defensive response. Thus, this study suggests that AITC has several roles in plant defense and add evidence to the growing data supporting a multifunctional role of glucosinolates and their degradation products in plants.